Association between Maternal High BMI and the Birth Weight of Neonates in Diabetic and Non-Diabetic Group - Kabir, Rezwana; Islam, Farhana; Begum, Ferdousi; Chowdhury, TA (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Background: Body mass index (BMI) has increased among the women of reproductive age worldwide. Increased insulin resistance associated with obesity and diabetes are mostly responsible for adverse outcomes like macrosomia, maternal morbidity, increased operative interference, longer hospital stays and increased neonatal complications. Objectives: To assess maternal high BMI and its association with the birth weight of neonates in diabetic and non-diabetic groups. Methods: A cross sectional study was conducted in the obstetrics Department of BIRDEM General Hospital Dhaka during July 2017 to June 2018 on 200 pregnant women with high BMI (>23.1 kg/m 2 ) at 3 rd trimester. Patients were allocated in two groups- Group I (Diabetic-100 patients) and group II (non-diabetic -100 patients). Data was collected in a structured data collection sheet with informed written consent. Result: Age range was 18 to 35 years with mean age of 26.9 ± 8.3 years among diabetic and 25.7 ± 7.8 years among non-diabetic women. Maximum number of participants were socioeconomically in the middle class 117 (58.5%) group. BMI was comparatively higher in diabetic group but the difference was not statistically significant. Among 27% overweight, 18% were in diabetic and 36% were in non-diabetic group. On the other hand, 53% were obese (58% in diabetic and 48% in non-diabetic group); 20% were morbidly obese (24 % diabetic and 16 % non-diabetic). About 23(11.5%) of the babies had a birth weight more than 3.5 kg (maximum among diabetic mothers, 15% vs 8% in group I & II respectively). Only 6 babies were macrosomic (BW >4 Kg) in this study & all of their mothers had diabetes. The mean birth weight was higher in diabetic group 3.7 ± 0.4 kg vs 2.6 ± 0.5 kg in non-diabetic group respectively and the result was statistically significant. Conclusion: High BMI diabetic mothers have significantly higher mean birth weight of their newborns. Bangladesh J Obstet Gynaecol, 2021; Vol. 36(2): 107-113